Effects of whole-body vibration on body composition, microbiota, cardiometabolic markers, physical fitness, and quality of life after bariatric surgery: protocol for a randomized controlled trial - Alejandro Gómez-Bruton; Pilar Irún; Angel Matute-Llorente; Gabriel Lozano-Berges; Ana Moradell; Susana Ara-Gimeno; Jorge Subias-Perie; Marta Sánchez-Luengo; Gonzalo Hijos-Mallada; Sandra García-Mateo; Samantha Arechavaleta; María José Palacios Fanlo; et al. (Trials, 2024)
Abstract Background Morbid obesity is a complex chronic condition characterized by a body mass index of 40 kg/m2 or higher. The incidence of the condition is on the rise in developed countries, and bariatric surgery has been proposed as a potential solution to address this trend. Nonetheless, bariatric surgery may also result in adverse effects, including a reduction in bone mineral density (BMD) and muscle mass, as well as an increased risk of fractures. The present study aims to elucidate the effects of bariatric surgery and whole-body vibration (WBV) training on body composition, microbiota, physical fitness, quality of life, and cardiometabolic markers. Methods Twenty-eight participants (14 females), aged 18 to 50 years, will undergo sleeve gastrectomy surgery. They will be randomly allocated into a control group or a WBV training group. The WBV group will train three times per week with increasing intensities and duration ranging from 30 to 45 min over the 4-month training period. Measurements of body composition (dual-energy X-ray absorptiometry and peripheral quantitative computed tomography), physical fitness (muscular strength, agility, cardiorespiratory fitness, and balance), gait biomechanics, cardiometabolic markers, gut microbiota, quality of life, and physical activity levels will be collected at four different time points: (1) prior to the surgery, (2) 45 days post-surgery, (3) 6 months post-surgery, and (4) 18 months post-surgery. Discussion Both groups are expected to experience improvements in most of the aforementioned variables. Nonetheless, we expect the WBV group to show larger improvements proving that the training is effective and safe. Trial registration Clinicaltrials.gov NCT05695599. Registered on January 25, 2023.